The Culture-Research Nexus: Stakeholders’ Perceptions of the Connection between Disciplinary Cultures and Research Choices in Higher Education - Kaweesi, Muhamadi; Bisaso, Ronald; Ezati, Betty Akullu (African Journal of Education and Practice, 2018)
Within the higher education discourse, the critical role of disciplinary cultures in influencing organisational departmentalisation; shaping the academic profession; and in informing academic leadership has been underscored. However, the connection between disciplinary cultures and research choices seems to be underreported. The study explored key stakeholders’ perceptions of this connection in Uganda’s research-led flagship academic institution, Makerere University. The purpose was to ascertain whether and how the espoused disciplinary practices, values and beliefs inform the research choices of academics across disciplinary fields. We adopted a qualitative, intrinsic case study design that was rooted in social constructivism philosophy and guided by an interpretivist paradigm. Professorial staff and Institutional level senior research managers constituted the sample. Data were collected using in-depth interviews from four Full Professors, eight Associate Professors, and two institutional level senior research managers. We then triangulated data sources with documents checks. We analysed data thematically. Findings: Findings reveal that although there is a connection between disciplinary cultures and research choices, the ethos of producing knowledge at the very basic level has more influence on academics' research choices. This is because, across disciplinary fields, research is more understood in terms of journal articles. Unique contribution to theory, practice and policy: We recommend that if the University is to perfect her research-led status, there is need to popularise cultures that would promote the production of diverse knowledge in order to enhance the contribution of the University to national socio-economic development. This could be achieved by revising the existing research policies to ensure that when academics are being assessed for promotion, they should be assessed on a broader criterion that includes number of publications and contribution to policy and the community.
Keywords: Disciplinary cultures, Research choices, Higher education